Xist upstream deletion leads to dysregulation of Xist and autosomal gene expression - Majumdar, Sudeshna; Bammidi, Lakshmi Sowjanya; Naik, Hemant C.; Manhas, Avinchal; Baro, Runumi; Kalita, Akash; Naskar, Amlan Jyoti; Nidharshan, Sundarraj; Bariha, Girija S.; Notani, Dimple; Gayen, Srimonta

(untitled) (Genome Research, 2025)
Xist long noncoding RNA is the master regulator of the X-Chromosome inactivation (XCI) process. Xist is expressed from the inactive X and coats the inactive X to facilitate XCI. Cis-regulation of Xist expression remains poorly understood in the context of maintenance of XCI. Here, we have explored the role of the Xist upstream sequences (∼6 kb) lying between Tsix and Jpx in the regulation of Xist and XCI in mouse extra-embryonic endoderm stem cells (XEN), which represent the maintenance phase of imprinted XCI. Here, we show that the deletion of this Xist upstream sequence in the inactive X leads to the upregulation of Xist expression accompanied by the dispersal of the Xist cloud. Notably, we find the loss of enrichment of repressive marks such as H3K27me3, H4K20me1, and MacroH2A, except that of H2AK119ub, in dispersed Xist nuclei. However, X-linked genes remain silent despite Xist dispersal and loss of enrichment of repressive marks. Notably, we find that many autosomal genes, including cohesin Rad21, are dysregulated in Xist-upstream-deleted cells. Additionally, we demonstrate that Xist-upstream deletion leads to alterations of topological contacts of the Xist locus with its upstream positive regulator Ftx and across the inactive X and autosomes. Finally, we show genome-wide alterations of the occupancy of architectural proteins CTCF/RAD21, including at many loci of the inactive X such as the Xist upstream regions and the Firre locus, which is critical for maintaining inactive X conformation. Taken together, we demonstrate that the Xist upstream sequence imparts a multifaceted role in genome regulation beyond the XCI.